ACCURACY OF WORD ORDER IN PHRASES AND SENTENCES RESULTING FROM MACHINE TRANSLATION - Lina Anisah; Ratna Dewanti; Yumna Rasyid (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study examines the accuracy of word order in phrases and sentences generated by machine translation. Machine translation, using natural language processing technology, has shown great progress in translating text between languages. However, obstacles still occur, especially in the context of complex sentences and language nuances. This study will analyze various studies related to this using the Systematic Literature Review (SLR) method. In this study, a review and identification of all articles published between 2013-2023 were conducted. After an extensive search, 25 articles were obtained that met the criteria. This article illustrates that machine translation tends to provide the best results on simple sentences, while accuracy can vary in more complex situations. Manual revision by humans is still required to ensure accuracy and consistency in word order, demonstrating the importance of understanding context and linguistic nuances in the development of more sophisticated machine translation.